EKARISTI YANG PERTAMA? : Analisa Biblis Tindakan Yesus berdasarkan Injil Markus 8:1-9 - Hermas Asumbi; Fabylio Cornelius Togas (Pineleng Theological Review, 2026)
Throughout His life, Jesus performed many miracles. One of the compelling miracle stories is the multiplication of the loaves, as found in the Gospel of Mark 8:1-9, where Jesus fed 4,000 people. Jesus' actions in this story are often associated with the Eucharistic Liturgy. This narrative is intriguing because, although frequently considered a duplicate of the feeding of the five thousand (Mark 6:30-44), this pericope possesses significant terminological and theological differences from the Mark 6 account regarding the Eucharistic Action itself. This paper aims to analyze the story of Jesus feeding the four thousand in Mark 8:1-9 to explore the biblical foundation of the Sacrament of the Eucharist. This research seeks to provide an analysis of whether the narrative of Mark 8:1-9 truly represents a Eucharistic action performed by Jesus for the first time, or is merely a story retold by the evangelist. Through textual-narrative, social, and Jewish tradition approaches, the author finds that Mark 8:1-9 more specifically reflects the liturgical practices of the early church. This is evident from the use of the verb eucharistēsas (giving thanks) in chapter 8, which differs from the word eulogēsen (blessing) used in Mark 6:30-44.